Analisis Pengaruh Kualitas Pelayanan dan Fasilitas Lingkungan Terhadap Kepuasan Penyewa Pada PT. Plaza Nusantara Realty - Boby Kristian Lase; Rakhmat; Murdan Sianturi (Mulia Pratama, 2024)
The author's goal is to conduct research to determine the effect of service quality on tenant satisfaction at Plaza Indonesia mall, to determine the effect of environmental facilities on tenant satisfaction at shopping centers or Plaza Indonesia malls. The sampling technique used is non-probability sampling. Non-probability sampling is defined as a sampling technique in which the researcher selects a sample based on the researcher's subjective judgment rather than random selection. The number of samples used in this study were 50 respondents as tenant employees or tenants at Mall Plaza Indonesia. The results of this study were collected through questionnaires which were processed and analyzed using multiple linear regression. Then to test the quality of the data used is the validity test and reliability test. To test the hypothesis in this study. Researchers used the t test and F test and carried out a determination test. After conducting the analysis the authors draw the following conclusions: 1) Based on multiple linear regression calculations it is known that environmental facilities have an influence on tenant satisfaction 2) From the t-test results there is a significant and significant influence between the variables of environmental facilities and tenant satisfaction 3) From the test results F and the results of the Coefficient of Determination test show that there is a positive influence between service quality and environmental facilities which together on tenant satisfaction